CNT‐Strung LiMn2O4 for Lithium Extraction with High Selectivity and Stability. Issue 7 (12th May 2022) - Shang, Xiaohong; Liu, Jianyun; Hu, Bin; Nie, Pengfei; Yang, Jianmao; Zhang, Boshuang; Wang, Yiwen; Zhan, Fei; Qiu, Jieshan
Abstract: LiMn2 O4 is of great potential for selectively extracting Li + from brines and seawater, yet its application is hindered by its poor cycle stability and conductivity. Herein a two‐step strategy to fabricate highly conductive and stable CNT‐strung LiMn2 O4 (CNT‐s‐LMO) is reported, by first stringing Mn3 O4 particles with multiwalled carbon nanotube (CNT), then converting the hybrids into CNT‐s‐LMO through hydrothermal lithiation. The as‐synthesized CNT‐s‐LMO materials have a net‐like structure with CNTs threading through LMO particles. This unique structure has endowed the CNT‐s‐LMO electrode with excellent conductivity, high specific capacitance, and enhanced rate performance. Because of this, the CNT‐s‐LMO electrode in the hybrid capacitive deionization cell (HCDI) can deliver a high Li + extraction percentage (≈84%) in brine and an outstanding lithium selectivity with a separation factor of ≈181 at the Mg 2+ /Li + molar ratio of 60. Significantly, the CNT‐s‐LMO‐based HCDI cell has a high stability, evidenced by 90% capacity retention and negligible Mn loss in 100 cycles. This method has paved a new way to fabricate carbon‐enabled LMO‐based absorbents with tuned structure and superior capacity for electrochemical lithium extraction with high Li + selectivity and exceptional cycling stability, which may help to tackle the shortage in supply of Li‐ion batteries in industry in the future. Abstract : CNT‐strung LiMn2 O4 (CNT‐s‐LMO) is synthesized by a two‐step strategy, in which the Mn3 O4 particles are first strung with multiwalled carbon nanotube (CNT), and then the obtained hybrids are converted into CNT‐s‐LMO through hydrothermal lithiation. When being used in the hybrid capacitive deionization cell (HCDI), the CNT‐s‐LMO electrode delivers superior selectivity and exceptional stability for lithium extraction from brine.